Pengujian Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan - Adhika Raharja Putra; Yefta Andi Kusnoegroho (AFRE (Accounting and Financial Review), 2021)
A good financial report produced by the company is a reflection of the actual condition of the company and there are no errors. However, management performance is sometimes not as good as expected, so that financial statement fraud can occur for the sake of a good company image. This study is a quantitative study that aims to examine the effect of the pentagon fraud as proxied by eight consisting of three variables from the pressure element (financial target, financial stability, external pressure), two variables from the opportunity element (ineffective monitoring, external auditor quality), one the variable from the element of rationalization (change in auditor), one variable from the element of competence (change in director) and one variable from the element of arrogance (frequent number of CEO's picture) on the existence of fraudulent acts of financial statements. This study uses secondary data with purposive sampling, there are 16 consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2017-2020. The results of this study prove that the variables of pressure and arrogance have a positive influence on the existence of fraudulent acts of financial statementsl